La construction de la cause végétarienne au prisme du genre : engagements, circulations et réseaux transnationaux entre France, Suisse, Angleterre et Belgique (années 1870-1914) - Alexandra Hondermarck (Genre & Histoire)
This article examines the vegetarian movement that developed in France from the end of the nineteenth century around the Société végétarienne de France, through the prism of gender. It focuses firstly on women’s involvement in the vegetarian cause, alongside their involvement in other causes such as the women’s rights movement or the leagues against vivisection and alcoholism, and secondly on the role of women in the arguments promoting vegetarianism. It appears that women, because of the nourishing, educational and reproductive functions attributed to them, are one of the main targets of “food reform”. Moreover, vegetarianism challenges dominant dietary norms that promote meat consumption as a source of strength and virility, leading vegetarians to redefine the gender norms associated with these dietary practices. Finally, we show that women play an increasingly important role within the vegetarian movement over time, and a crucial role in putting the diet into practice.